Legal Protection for Workers with Disabilities in Indonesia: Regulatory Analysis, Implementation Challenges, and Efforts to Improve Implementation - Satrya Ramadhan Anggara; Nurhasanah Br Sinulingga (ISNU Sumatera Utara, 2024)
This study aims to analyze regulations regarding the protection of workers with disabilities in Indonesian legislation, as well as to identify challenges in implementing legal protection and efforts to improve its implementation. This study uses a normative juridical method. The research stages include problem formulation, collection of primary, secondary, and tertiary legal materials, and normative analysis through systematic and conceptual interpretation. The object of study is norms in Law No. 8/2016and Law No. 13/2003, as well as relevant scientific literature. The results of the study indicate that legal protection for workers with disabilities in Indonesia has been regulated through a legal framework, which guarantees the right to non-discrimination, reasonable accommodation, equal wages, OSH, and social security for workers. However, its implementation still faces various challenges, such as weak law enforcement, minimal reasonable accommodation, discrimination and stigma, regulatory disharmony, and limited inclusive job training. This study also found that efforts to strengthen regulations, implement sanctions and inclusive audits, provide reasonable accommodation, improve job training, and change work culture are strategic steps to improve this legal protection. The results also confirm that there is a gap between legal norms and employment practices, so that more concrete and sustainable policy interventions are needed.